Analysis of seed oils from selected edible fruits from Sarawak - Nurul Liana, Mohd Khalid (Universiti Malaysia Sarawak, UNIMAS, 2013)
Shorea Macrophylla, Castanopsis sp. and Canarium indicum are exotic fruits of Sarawak. These edible fruits are well known among local people in Sarawak. The fruit samples will be collected from certain areas in Sarawak. Extraction through ‘Bligh and Dryer’ has been done onto the fruits to obtain oil. In addition, extraction will be the main important step in this project to have a good yield of oil before it will be analyses through gas chromatography. Next, the oil content will be determined using gas chromatography-mass spectrometer (GC-MS). The composition of fatty acids of selected fruits has been identified by respective methods. Besides, minerals content has been determined through a method that has been done by certain researchers. Atomic Absorption Spectrophotometer (AAS) has been used to identify the elements content in seed of fruit.